1965
DOI: 10.1139/m65-117
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Extracellular Polysaccharides by the Blue-Green Alga Anabaena Flos-Aquae

Abstract: Extracellular polysaccharides were isolated from the blue-green alga Anabaena flos-aquae strain A-37. The polysaccharides are composed of glucuronic acid, glucose, xylose, and ribose in a molar ratio of 1:88:39:3. The extracellular polysaccharides comprise about 40% of the total carbohydrate produced by this alga.Carbon utilization experiments revealed that only D-fructose could be substituted for carbon dioxide as a precursor of polysaccharides and cellular material.The extracellular polysaccharides are deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The few available data seem to support this hypothesis: indeed, at least for A. £os-aquae [59,66], some Phormidium strains [53] and C. capsulata [63], the capsular and the released polysaccharides showed the same monosaccharide composition; in the case of C. capsulata, the two polymers also showed quite similar molecular masses (our unpublished results). With regard to the morphological changes that may occur during polysaccharide release, it was observed that, in C. capsulata [63] and Cyanothece 16Som2 [48], the thickness of the capsule surrounding the cells remained almost constant throughout growth phases and under all the culture conditions tested, in spite of the large amounts of polysaccharide released into the culture medium.…”
Section: Exopolysaccharide Release and Factors A¡ecting Polymer Produmentioning
confidence: 74%
“…The few available data seem to support this hypothesis: indeed, at least for A. £os-aquae [59,66], some Phormidium strains [53] and C. capsulata [63], the capsular and the released polysaccharides showed the same monosaccharide composition; in the case of C. capsulata, the two polymers also showed quite similar molecular masses (our unpublished results). With regard to the morphological changes that may occur during polysaccharide release, it was observed that, in C. capsulata [63] and Cyanothece 16Som2 [48], the thickness of the capsule surrounding the cells remained almost constant throughout growth phases and under all the culture conditions tested, in spite of the large amounts of polysaccharide released into the culture medium.…”
Section: Exopolysaccharide Release and Factors A¡ecting Polymer Produmentioning
confidence: 74%
“…Sulphated and 0-methyl sugars, common among eukaryotic extracellular polysaccharides (Percival, 1979;McCandles, 198 1 ;Painter, 1983), have yet to be reported (Sutherland, 1985). Chemical analyses of the slime layers of certain cyanobacteria have revealed an array of uronic acid and neutral sugar residues similar to those found in bacterial external layers (Hough et al, 1952;Bishop et al, 1954;Moore & Tischer, 1965;Dunn & Wolk, 1970;Kokyrsta & Chekoi, 1972;Sangar & Dugan, 1972;Wang & Tischer, 1973;Mehta & Vaidya, 1978;Painter, 1983). The more structurally resilient sheaths of Chlorogioeopsis PCC 69 12 (Schrader et al, 1982), Gfoeothece PCC 6501 (Jurgens & Weckesser, 1985) and Chroococcus minutus SAG B.41.79 (Adhikary et al, 1986) have been shown to contain 0-methyl sugars and a protein component, in addition to the typical sugar residues detected in previously studied external layers.…”
Section: Introductionmentioning
confidence: 80%
“…The species are diverse with respect to the ecological niches they occupy. Anabaena variabilis ATCC 29413 is a planktonic freshwater organism isolated from the Mississippi and misinterpreted as Anabaena flos-aquae (Moore & Tischer, 1965;Thiel et al, 2014). For this lifestyle, the akinetes may require a lipid envelope layer to survive at the bottom of sediments.…”
Section: Intracellular Storage Compounds Of Akinetesmentioning
confidence: 99%